2015
DOI: 10.1007/s12104-015-9613-3
|View full text |Cite
|
Sign up to set email alerts
|

1H, 13C and 15N assignments of EGF domains 8–11 of human Notch-1

Abstract: The Notch receptor is part of a core cell-cell signaling system crucial for development and tissue homeostasis in Metazoa. Structural information is available for the negative regulatory region, the ligand-binding region and the intracellular domain of Notch, but data for the remaining portions of the extracellular region which determine its overall shape at the cell surface are still lacking. This region consists of 36 EGF-like domains arranged as multiple tandem repeats. Most EGF-like domains near the ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Protein expression, isotopic labeling, refolding, and purification protocols have been described previously ( Muranyi et al., 2004 , Weisshuhn et al., 2015a , Weisshuhn et al., 2015b , Whiteman et al., 2014 ). Protein fragments were expressed in Escherichia coli BL21 cells transformed with a pQE30 (Qiagen)-based protein expression construct and a pREP4 plasmid for control of expression via the Lac Repressor.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Protein expression, isotopic labeling, refolding, and purification protocols have been described previously ( Muranyi et al., 2004 , Weisshuhn et al., 2015a , Weisshuhn et al., 2015b , Whiteman et al., 2014 ). Protein fragments were expressed in Escherichia coli BL21 cells transformed with a pQE30 (Qiagen)-based protein expression construct and a pREP4 plasmid for control of expression via the Lac Repressor.…”
Section: Methodsmentioning
confidence: 99%
“…Resonance assignments for EGF4-7, EGF8-11, and EGF11-13 have been described previously ( Muranyi et al., 2004 , Weisshuhn et al., 2015a , Weisshuhn et al., 2015b ) (Biological Magnetic Resonance Bank accession numbers 25172, 25533, 6031). 3D 15 N-edited total correlation spectroscopy-heteronuclear single quantum coherence (HSQC) and NOE spectroscopy (NOESY)-HSQC spectra were collected to assign the 1 H- 15 N HSQC spectrum of EGF7-9.…”
Section: Methodsmentioning
confidence: 99%
“…However, X-ray structures of EGF repeats 4–7 from human Notch1 (Weisshuhn et al, 2015a) show a striking tilt angle of ~90° between repeats 5 and 6, which doesn’t bind Ca ++ (Figure 1). To analyze additional tilt/twist angles between EGF repeats, the authors used NMR spectroscopy with constructs corresponding to Notch1 EGF repeats 4–7, 7–9, 8–11, and 11–13 (Weisshuhn et al, 2015b). These studies confirmed that Ca ++ binding EGF repeats assume a rigid rod like structure.…”
Section: ) Structural Biology Illuminates Receptor-ligand Interactiomentioning
confidence: 99%